Peningkatan Pemahaman Dasar Pola Makan Sehat guna Penanggulangan Stunting di Desa Kebonharjo, Kecamatan Polanharjo, Kabupaten Klaten - Wahyu Dwi Saputra; Aulia Maharraning Mustikawati; Devani Adinda Putri (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Nutritional problems with chronic conditions caused by certain situations, one of which is an unhealthy diet, is one of the factors that cause stunting. Referring to the Indonesian Nutrition Status (INS) data for 2022 and 2021, stunting in Klaten Regency is at 18.2% in 2022, a significant increase from 2021, which was recorded at 15.8%. Based on this, a socialisation activity with the title "Healthy Diet and Stunting Prevention" was carried out with the target of pregnant women, mothers of toddlers, and mothers of PKK Induk Kebonharjo Village, Polanharjo District, Klaten Regency, Central Java Province. The method used in this program was questionnaires, pre-test, and post-test to find out the direct impact after the socialisation was carried out. Based on the questionnaires distributed, 79.3% of participants had attended socialisation or other seminars on stunting before. Even so, the pre-test results showed an average score of 60 points, which is an indicator that re-understanding the concept of stunting and its handling is feasible. The post-test results showed an average participant score of 100 points, this shows that the socialisation that has been carried out has succeeded in providing the latest understanding of healthy eating patterns as one of the preventive ways to overcome stunting, especially in Kebonharjo Village.